Pieri type rules and GL(2|2) tensor products - Heidersdorf, Thorsten; Weissauer, Rainer (Algebras and representation theory, 2021)
We derive a closed formula for the tensor product of a family of mixed tensors using Deligne’s interpolating category $\underline {Rep}(GL_{0})$. We use this formula to compute the tensor product of a family of irreducible GL(n|n)-representations. This includes the tensor product of any two maximal atypical irreducible representations of GL(2|2).
Published online: 19 March 2020
Gesehen am 22.06.2021